2019
DOI: 10.11301/jsfe.19546
|View full text |Cite
|
Sign up to set email alerts
|

High Voltage Pulsed Electric Field Application Using Titanium Electrodes for Bacterial Inactivation in Unpurified Water

Abstract: Pulsed Electric Field (PEF) treatment is considered as nonthermal due to application of ultra short high voltage pulses in liquid foods to extend their shelf life. In today's world, water decontamination becomes extremely necessar y to safeguard people from health ailments. The objective of this work focusses on inactivation of naturally prevailing Escherichia coli and Fecal coliform bacteria in environmental water using titanium electrodes. In this study, the PEF treatment chamber was designed to be used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…However, the results of our current experiment showed no significant difference in the disinfection effect between the AC voltage and the positive pulse voltage. Nevertheless, our findings confirm that the increase in the disinfection rate aligns with previous studies, occurring due to the rise in electric field intensity applied across all voltage types, including DC, AC, and pulse voltages [ 34 , 35 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. We also observed a correlation between the bacterial disinfection rate and the applied voltage frequency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the results of our current experiment showed no significant difference in the disinfection effect between the AC voltage and the positive pulse voltage. Nevertheless, our findings confirm that the increase in the disinfection rate aligns with previous studies, occurring due to the rise in electric field intensity applied across all voltage types, including DC, AC, and pulse voltages [ 34 , 35 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. We also observed a correlation between the bacterial disinfection rate and the applied voltage frequency.…”
Section: Discussionsupporting
confidence: 92%
“…Enhancing the sterilization effect may involve increasing the electric field strength or concentrating the field on the cell membrane. Studies by Hayamizu et al (1989) and Ramaswamy et al (2019) explored electrode shapes and materials, with Hayamizu et al investigating tissue destruction around electrodes using plate and coaxial needle electrodes, and Ramaswamy et al comparing titanium and stainless-steel electrodes, revealing that, at an equivalent field strength of 24 kV/cm, the titanium electrode displayed superior effectiveness in killing two types of microorganisms at lower temperatures [ 40 , 41 ]. Kitajima et al (2007) demonstrated that sterilization rates depend on factors such as fiber electrode wire gap length, bacterial suspension conductivity, electrode surface area, and flow velocity [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of the variations of current density change as function of the bubble diameter was carried out [17] demonstrating an exponential increment of the current density with the electrode coverage by a gas film. The variation of the local current density can affect some electroporation treatments based on the amount of applied energy, like a inactivation of bacteria, antibiotics and another cellular organisms [18][19][20], extraction of bio-components [21][22][23], gen therapy [24,25], microfluidics chamber designs [26,27], food industry processes [28,29], hydrogen production [30] and another process based of the mass transfer area [31,32]. Another undesirable effect of the current density changes is the increase of temperature and dielectric breakdown [33,34] as a function of electrical conductivity [35].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biofilms have proven to be very resistant to several types of antibiotics and chemical disinfectants (Eriksson, 2011), making it difficult to inhibit their growth. Therefore, a right sterilization technique that can reduce the number of bacteria quickly but also does not cause heat to the materials of medical devices is highly needed, such as sterilization using high-intensity electric fields (Ramaswamy et al, 2019;Bonetta et al, 2014). In fact, the interaction between high-intensity electric fields with bacteria causes irreversible electroporation to the cell membrane (Miklavčič, 2017), which in turn induces bacterial death (Rosin & Kurrasch, 2018).…”
Section: Introductionmentioning
confidence: 99%